1978
DOI: 10.1002/j.2050-0416.1978.tb03891.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Sunstruck Flavour of Beer

Abstract: It has been confirmed that sunstruck flavour is due to the formation of 3-methyl-2-butene-1 -thiol formed by photolysis of iso-a-acids in the presence of sulphur-containing amino acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…4,5 The concentration of iso-˛-acids in the final beer is normally 10-40 mg l 1 , but they are unfortunately susceptible to degradation by oxidation and photochemical processes. 6 -10 The decomposition may lead to the formation of 3-methyl-2-butene-1-thiol that imparts an unpleasant aroma (sunstruck flavor 10,11 ) to the beer. The use of reduced iso-˛-acids was proposed four decades ago 12 as a possible solution to the degradation problem by preventing the formation of 3-methyl-2-butene-1-thiol.…”
Section: Are Isomerized Forms Of The˛-acids (Humulones) Originating Fmentioning
confidence: 99%
“…4,5 The concentration of iso-˛-acids in the final beer is normally 10-40 mg l 1 , but they are unfortunately susceptible to degradation by oxidation and photochemical processes. 6 -10 The decomposition may lead to the formation of 3-methyl-2-butene-1-thiol that imparts an unpleasant aroma (sunstruck flavor 10,11 ) to the beer. The use of reduced iso-˛-acids was proposed four decades ago 12 as a possible solution to the degradation problem by preventing the formation of 3-methyl-2-butene-1-thiol.…”
Section: Are Isomerized Forms Of The˛-acids (Humulones) Originating Fmentioning
confidence: 99%
“…2,3 Beer develops an off-flavour when exposed to light because of the formation of trace amounts of 3-methyl-2-butene thiol (4), and it has been shown that the iso-alpha acids must be present for this to occur (3)(4)(5). This thiol has a taste threshold in beer of about 10 -11 mol/L, and so extremely small amounts formed by photolysis of iso-alpha acids can generate an off-flavour (6)(7)(8). In the brewing industry, beer so afflicted is termed "light-struck" and more colloquially as "skunky", since the thiol has an odor similar to that associated with skunks.…”
Section: Introductionmentioning
confidence: 98%
“…Kuroiwa and Hashimoto [3] and Kuroiwa et al [6] described in the early 1960s the aroma active compound 3-methylbut-2-ene-1-thiol (MBT), out of odorless precursors, as being the key compound responsible for sunstruck flavor. This substance, with an aroma threshold in water of 0.2-0.4 ng/L [7] and of 4-35 ng/L [8] in beer, is considered one of the most important aroma active compounds. Komarek et al [8] identified in beer after exposure to sunlight, besides MBT, other substances such as 3-(methylthio)-propanal, phenylacetaldehyde, 2-methylpropanal, 3-methylbutanal and an unknown compound with a sulfury odor note.…”
Section: Introductionmentioning
confidence: 99%